A broader perspective on records as seen by Records-in-Contexts. Issue 1 (January 2018) - Popovici, Bogdan-Florin
Abstract : The new ICA standard Records-in-Contexts (R-i-C) takes the evolution of descriptive standards to the next level. The realities of digital recordkeeping, the increasing fluidity between "records" and "archives" – as recognised in Continuum thinking – and globalisation, have already made old boundaries between records managers and archivists less meaningful, and it is in this context that R-i-C is being developed. R-i-C can, for instance, be of direct use to records managers, in particular because the need to ensure usability and access of records over time has been pushed back to the start of the lifecycle, and because Open Data and Freedom of Information initiatives require integrated access to information sources. The R-i-C development process included alignment with ISO23801 Metadata for Records, meaning that using R-i-C will also facilitate compliance with ISO15489. The new multidimensional approach of R-i-C, along with its more conceptualised definitions of "entities" – for example of "Record" and "Record Set" – allows for more precise description, better contextualization and, therefore, improvements in the use and interpretation of records. R-i-C's conceptual model and its ontologies open the way for better integration of records descriptive practices, no matter what the long dividing lines of professions, traditions and approaches.